Pengabdian Masyarakat Mengenai Tuberkolosis Pada Anak di SDN 68 Kolo Kota Bima - Nurbaety Nurbaety; Sri Astuti; Putri Yayu (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
Community service through health education to children regarding tuberculosis in children is very important so that children can prevent the emergence of tuberculosis in children. The role of parents is very important in providing information every day as a reminder that the Puskesmas and Health Workers have provided Health Education through visits to schools in the Kolo Kota Bima environment, Increased knowledge related to tuberculosis in children to prevent tuberculosis in children by providing counseling at every elementary school in Kota Bima cooperates with health and government agencies. Based on the preliminary study, data were obtained on the number of children who knew about tuberculosis in children, there were 2 out of 10 children. The activity method is carried out by making pre and posttest questions that are used to measure the level of knowledge before and after being given counseling. Based on the results of the assessment before (pretest) counseling was given, namely 19 children (83%) who had less knowledge (83%) had sufficient knowledge (4 people (17%)). and experienced an increase after counseling was carried out by conducting a reassessment (posttest) where children who had less knowledge, namely 5 people (22%), 8 people (35%) were good and 10 people (43%) were good.